2008
DOI: 10.1007/978-3-540-88564-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Long-Term Use of the Gnowsis Semantic Desktop for PIM

Abstract: Abstract. The Semantic Desktop is a means to support users in Personal Information Management (PIM). Using the open source software prototype Gnowsis, we evaluated the approach in a two month case study in 2006 with eight participants. Two participants continued using the prototype and were interviewed after two years in 2008 to show their long-term usage patterns. This allows us to analyse how the system was used for PIM. Contextual interviews gave insights on behaviour, while questionnaires and event logging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…(Sauermann and Heim, 2008) describes such a long term study, here several participants used the system for their daily work for a period of two months, two of the users kept using the system and we also describe their experiences after using the system for a period of two years.…”
Section: Long Term Usabilitymentioning
confidence: 99%
“…(Sauermann and Heim, 2008) describes such a long term study, here several participants used the system for their daily work for a period of two months, two of the users kept using the system and we also describe their experiences after using the system for a period of two years.…”
Section: Long Term Usabilitymentioning
confidence: 99%
“…Gnowsis [Sa05], Nepomuk 7 ). Interestingly the results of this have often shown that users make more use of their own explicit ontologies, although the larger automatic data is clearly of value [SH08]. This underlines the need to ensure that underlying technologies are set within suitable user interaction, which in this case may be as simple as marking the provenance of data and selectively presenting it so that users are not swamped.…”
Section: Memory and Context: Personal Ontologies And Spreading Activamentioning
confidence: 99%
“…It has been shown [15] that the inclusion of semantic technologies on the desktop can significantly improve the user's perceived quality of personal information management, especially when they are applied during a longer time period.…”
Section: And Vocabulariesmentioning
confidence: 99%
“…This has two main benefits: first, it makes it possible to interrelate objects from different sources, which otherwise form disjunct structures in one's personal information space [3]; and second, it extends the possibilities provided by file systems with respect to search and retrieval [15]. All three classes of applications, as described before, could benefit from such an integration: user-driven file structures could be extended by more powerful and non-hierarchical annotation mechanisms, like tagging and typed relationships.…”
Section: Integrating File Systems and Rdf Descriptionsmentioning
confidence: 99%